Dominant Groups Have Right to Live? - Bhattachan, Krishna Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2006)
I have divided this paper into four sections: (1) Bio- and socio-cultural diversity, (2) Definition and identification of “tribals” in Nepal, (3) Tribals and Forests, and (4) Common issues of sustainable livelihood. Tribals and Forests are divided into two sub-sections: (i) Forest dwellers (nomads and settled forest dwellers) and (ii) Tribals who have been dispossessed from their forests and lands and now become forest dependent. I have identified four common issues of sustainable livelihood: (I) land alienation, (ii) displacement and deforestation, (iii) loss or exploitation of indigenous knowledge system, and (iv) lack of resistance, organized movements and insurgency. DOI: 10.3126/dsaj.v1i0.275 Dauligiri Vol.1 (2005) pp.42-66